An updated review of cold shock and cold stress in fish - Reid, Connor H.; Patrick, Paul H.; Rytwinski, Trina; Taylor, Jessica J.; Willmore, William G.; Reesor, Bob; Cooke, Steven J. (Journal of fish biology, 2022)
Temperature is critical in regulating virtually all biological functions in fish. Low temperature stress (cold shock/stress) is an often‐overlooked challenge that many fish face as a result of both natural events and anthropogenic activities. In this study, we present an updated review of the cold shock literature based on a comprehensive literature search, following an initial review on the subject by M.R. Donaldson and colleagues, published in a 2008 volume of this journal. We focus on how knowledge on cold shock and fish has evolved over the past decade, describing advances in the understanding of the generalized stress response in fish under cold stress, what metrics may be used to quantify cold stress and what knowledge gaps remain to be addressed in future research. We also describe the relevance of cold shock as it pertains to environmental managers, policymakers and industry professionals, including practical applications of cold shock. Although substantial progress has been made in addressing some of the knowledge gaps identified a decade ago, other topics (e.g., population‐level effects and interactions between primary, secondary and tertiary stress responses) have received little or no attention despite their significance to fish biology and thermal stress. Approaches using combinations of primary, secondary and tertiary stress responses are crucial as a research priority to better understand the mechanisms underlying cold shock responses, from short‐term physiological changes to individual‐ and population‐level effects, thereby providing researchers with better means of quantifying cold shock in laboratory and field settings.